Introduction to Severe Storms and Hazardous Weather - Halverson, Jeffrey B; Robenhorst, Thomas D (New york : Routledge/Taylor & Francis, 2024)
This book presents a deep and encompassing survey of severe weather in all its forms. An Introduction to Severe Storms and Hazardous Weather is an exciting new textbook that allows students to learn the principles of atmospheric science through the drama, exhilaration, and even tragedy of severe weather.Balancing breadth and depth, Jeffrey B. Halverson adeptly combines a short, accessible introduction to the basic principles of meteorology with detailed coverage on large- and small-scale weather hazards. He draws on specific up-to-date case studies from North America to illustrate the cause of meteorological events including hurricanes, heavy snow and ice, floods, and tornadoes. Unlike existing books on the market, Halverson delves deep into the societal impacts of these events, drawing on examples from agriculture, utility infrastructure, and commercial aviation. Each chapter also features high-quality, customized color artwork by Thomas D. Rabenhorst that helps to enhance and embed learning.Thorough in its scope, and written with an impeccable focus on the science, this book will be an essential resource for introductory undergraduate courses in severe weather, natural hazards, and extreme meteorology. It is also an excellent supplemental textbook for courses on meteorology and atmospheric science.
Includes appendix and index.
Keywords: Meteorology; Severe storms; Floods; Hurricanes; Tornadoes